Application of eye-tracking technology to compare how instant lemongrass drink packaging imagery influences customer interest - Kuntaros, Suchada; Rattanakasamsuk, Kitirochna; Tangkijviwat, Uravis; Chinda, Kanok (Journal of Graphic Engineering and Design, 2025)
The research aimed to compare how different styles of instant lemongrass drink package imagery influence consumer interest and behavior using eye-tracking technology. A total of 30 participants, aged 19 to 65, evaluated three packaging styles: style 1 Images of instant lemongrass drinks served in a cup, style 2 images of instant lemongrass drinks served in a cup with steam and style 3 images of instant lemongrass drinks being poured into a cup. To determine visual areas of interest (AOIs), we examined eye-tracking variables including number of fixations, duration of fixations, and heatmaps. To mitigate positional bias, we displayed each style at a randomly assigned screen position each time. Participants also filled out a survey to determine which style they would most likely purchase. A one-way ANOVA and Tukey HSD post-hoc testing revealed significant variations in fixation metrics among the styles. The result demonstrates style. Two images of instant lemongrass drinks served in a cup with steam had the longest average duration of fixations and were the most popular style that affected customer choice. This is due to the warm sensation they experience when they gaze at it, which is associated with their preference for hot tea over cold tea, as well as the sensation of being close to a product as if it were in front of them. The findings highlight the necessity of using dynamic emotional packaging imagery and resonant visual features in packaging. This study makes actionable ideas for packaging designers and marketers to increase customer engagement and product awareness in competitive markets.